İmmobilize siklodekstrin glikoziltransferaz kullanılarak ? ß ? siklodesktrin üretimi - Yılmaz, Şule (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2009)
Siklodekstrinler nişastadan elde edilen ve ? -(1--4) bağları ihtiva eden altı, yedi yada sekiz glikozdan oluşan siklik bileşiklerdir.Bu bileşikler çok sayıda farklı bileşiklerle kompleks oluşturur. Bundan dolayı siklodekstrinler ile kompleks oluşturabilen moleküllerin kimyasal kararlılığı, çözünürlüğü ve uçuculuğu değiştirilebilir.Endüstriyel olarak üretilen siklodekstrinler tarım, ilaç, kimya ve çevre endüstrisinde yaygın bir şekilde kullanılmaktadırlar.Bu çalışmada immobilize Thermanoanaerobacter Siklodekstrin glikoziltransferaz, Divinil Benzen-Stiren-Poligluteraldehit polimerine kovalent olarak immobilize edildi ve patates nişastasından siklodekstrin (? ß ?) üretiminde kullanıldı. Enzim %95±10 verimle immobilize edildi ve 15 batch reaksiyon süresinde aktivitede azalma olmadığı bulundu.

Cyclodextrins obtained from starch, are cyclic compounds usually containing six, seven or eight glucose molecules linked by ? -(1--4) linkages.Cyclodextrin form inclusion complexes with many different compounds. Thus, cylodextrins can alter solubility, volatily and the chemical stability of compounds which have the ability to form complexes with cyclodextrins.Cyclodextrins have been produced in large quantity and found many uses in different fields such as chemistry, agriculture and medicine.Using potato starch and cyclodextrin glycosyltransferase, we have produced cyclodextrin in %95±10 yield. Divinylbenzene-Styrene-Polygluteraldehyde polymer is used for immobilization matrix. Enzyme was immobilized to polymer by covalent binding method. Soluble enzyme hydrolysis cyclodextrins which produced, but immobilized enzyme was eliminated this problem.
Preparation of ? ß ? cyclodextrins using immobilized cyclodeztrin glycosyltransferase
Keywords: Biyokimya; Biochemistry